Vulnerability of Social Institutions - Fall, Falilou (OECD Economic Policy Papers, 2014)
Social institutions face many challenges. The recent economic crisis has provided a stress test as it has left a legacy of high unemployment and high government debt in many countries. It also lowered potential output and thus the revenue base for social protection schemes. At the same time, ageing and other secular trends raise long-term sustainability issues. The design of social institutions determines their capacity to deal with shocks and trend changes and the way risks are shared between the institutions and their stakeholders. They also circumscribe the scope for automatic or discretionary adjustments, when trade-offs between sustainability, adequacy and efficiency arise. This report examines the sustainability of social institutions and their ability to absorb and cope with short-term shocks and longer-term trends by providing risk sharing and expenditure smoothing, focusing on pension, health care and unemployment insurance schemes